Analisis Perbedaan Pengetahuan Gizi Kerja Pada Pegawai Instansi Pemerintah Di Kota Jambi - Aswin, Budi; Ibnu, Ismi Nurwaqiah; Reskiaddin, La Ode (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
Occupational nutrition is a promotional and preventive effort that can be carried out to improve health status and work productivity. This research aims to analyze the effectiveness of implementing occupational nutrition for government agency employees in Jambi City. This research is in the form of quantitative research, a type of quasi-experimental design research in which there is an intervention group and a control group. In the intervention group, treatment was carried out by providing a work nutrition package. The population in this study were ASN employees at the PUPR Service, ASN employees at the Jambi City Manpower, Cooperatives, and MSMEs Department, and the sample obtained was 58 people, calculated using the experimental research formula. Data will be analyzed to determine the effectiveness of implementing occupational nutrition for government agency employees in Jambi City using the Mann-Whitney test with (α = 0.05). The results of the analysis showed there were differences in knowledge (p = 0.019) between intervention group employees and control groups of government agency employees in Jambi City. In conclusion, the occupational nutrition package is effective in improving knowledge related to work nutrition among employees of government agencies in Jambi City